2020
DOI: 10.1507/endocrj.ej19-0283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations of ovarian cancer-related genes from RNA-sequencing data for Japanese epithelial ovarian cancer patients

Abstract: Ovarian cancer has the highest mortality rate among gynecological cancers. Gene mutations are involved in the carcinogenesis, metastasis, and therapeutic response in ovarian cancer. However, the variety and proportion of gene mutation is not fully analyzed in Japanese ovarian cancer patients, especially, in those with recurrent tumors. In the present study, RNAsequencing was performed for 32 clinical ovarian specimens obtained from 24 Japanese patients (24 primary cancer specimens and 8 recurrent specimens pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In the present study, we aimed to identify functional lincRNAs predominantly expressed in ovarian cancer. We screened our RNA-seq data analyzed by NONCODE database [ 18 ] obtained from clinical specimens of normal ovarian tissues ( n = 6) and ovarian cancers ( n = 15) [ 15 , 16 ]. Screening NONCODE v4 transcripts abundantly expressed in ovarian cancer compared with normal ovarian tissues by ≥10-folds at an FDR q -value threshold <0.05, we identified 10 particular lincRNAs ( Table 1 ), including known oncogenic RNAs: competing endogenous lncRNA 2 for microRNA let-7b ( CERNA2 )/ human ovarian cancer-specific transcript 2 (HOST2) [ 19 ], urothelial cancer associated 1 ( UCA1 ) [ 14 , 20 , 21 , 22 ], and long intergenic non-protein coding RNA 958 (LINC00958) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, we aimed to identify functional lincRNAs predominantly expressed in ovarian cancer. We screened our RNA-seq data analyzed by NONCODE database [ 18 ] obtained from clinical specimens of normal ovarian tissues ( n = 6) and ovarian cancers ( n = 15) [ 15 , 16 ]. Screening NONCODE v4 transcripts abundantly expressed in ovarian cancer compared with normal ovarian tissues by ≥10-folds at an FDR q -value threshold <0.05, we identified 10 particular lincRNAs ( Table 1 ), including known oncogenic RNAs: competing endogenous lncRNA 2 for microRNA let-7b ( CERNA2 )/ human ovarian cancer-specific transcript 2 (HOST2) [ 19 ], urothelial cancer associated 1 ( UCA1 ) [ 14 , 20 , 21 , 22 ], and long intergenic non-protein coding RNA 958 (LINC00958) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…We next screened OIN1 -associated genes whose expression levels exhibited positive or negative correlations with OIN1 in the RNA-seq data from ovarian cancer specimens [ 15 , 16 ]. We found that 323 and 312 genes had correlation coefficients of ≥0.6 and ≤−0.45 with OIN1 , respectively, and analyzed enriched biological pathways in these identified genes using the DAVID Bioinformatics Resources 6.8 [ 24 ] ( Tables S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations